PREVALENCE OF OSTEOPOROSIS AND ITS IMPACT ON QUALITY OF LIFE OF PRE AND POST MENOPAUSAL WOMEN - Wajeeha Ishtiyaq; Arslan Tariq; Azka Fatima (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Background: Globally, osteoporosis is one of the major health concerns as there is a drastic increase in incident of osteoporotic related fractures. It is a silent bone disease which is characterized by a progressive decrease in bone mass and density(2). In Pakistan, occurrence of osteoporosis is quite common among females and negatively affects patient’s quality of life.(6)